IMPACT OF AUGMENTED REALITY-BASED NEURONAVIGATION ON NEUROSURGICAL EDUCATION AND TRAINING - Aydın Aydoseli; Sefa Öztürk; Eren Andıç; Mustafa Selim Şahin; Tahir Kaplan; Çağatay Ündeğer (İstanbul Tıp Fakültesi Dergisi)
Objective: Integrating technology into surgical training enhances learning experiences. Affordable extended reality (XR) equipment, like the Illumetry XR screen with ArSurgeon software, allows segmentation of preoperative MRI and CT scans in a digital environment, presenting 3D visualisations of tumours and surrounding anatomy. This improves the spatial orientation and understanding of surgical cases, benefiting neurosurgery residents. Material and Methods: This study utilized preoperative MRI and CT scans of two patients, one with a right frontal mass and the other with a pituitary adenoma. The scans were segmented to isolate the brain, mass, and vascular structures. The 3D models were integrated with MRI and CT data and examined on the Illumetry XR screen with ArSurgeon software. Surgical procedures were recorded and edited into 5-minute videos. Forty neurosurgery residents, split into two groups based on the training year, were provided with the scans and 3D models. After viewing the surgical video, the participants completed a 20-item survey. The survey results were analysed using IBM SPSS Statistics version 29.0. Result: Among the 40 participants (28 male, 12 female), half were in the first three years of training, and half had 3-5 years of experience. The AR-based neuronavigation system received an average motivation score of 8.4/10, an ease of use rating of 7.6/10, and an ergonomic design rating of 7.9/10. Participants also rated the system’s contribution to anatomical understanding and mastery at 8.3/10. Conclusion: The study showed that AR-based neuronavigation systems effectively enhance surgical education by motivating learners and improving anatomical knowledge. However, further improvements in ergonomics and design could enhance their utility in medical training.